Gold-catalyzed synthesis of glyoxals by oxidation of terminal alkynes: one-pot synthesis of quinoxalines - Shi, Shuai; Wang, Tao; Yang, Weibo; Rudolph, Matthias; Hashmi, A. Stephen K. (Chemistry - a European journal, 2013)
From terminal alkynes to glyoxals: Terminal alkynes can be oxidized under mild conditions by the use of an N-oxide in the presence of a gold catalyst. The intermediate glyoxal derivatives can be transferred in a one-pot procedure to substituted quinoxalines (see scheme).
Published online: April 9, 2013
Gesehen am 26.01.2022